2021
DOI: 10.1038/s41598-021-81961-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and regulatory T cell genes are differentially expressed in peripheral blood mononuclear cells of Parkinson’s disease patients

Abstract: Our aim was to identify the differentially expressed genes (DEGs) in peripheral blood mononuclear cells (PBMC) of Parkinson’s disease (PD) patients and healthy controls by microarray technology and analysis of related molecular pathways by functional annotation. Thirty PD patients and 30 controls were enrolled. Agilent Human 8X60 K Oligo Microarray was used for gene level expression identification. Gene ontology and pathway enrichment analyses were used for functional annotation of DEGs. Protein–protein intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 91 publications
(108 reference statements)
1
14
0
Order By: Relevance
“…Upregulation in the oxytocin signalling pathway is also seen to increase the expression of cPLA2 and also increase the calcium ion flux inside the cell (Soloff et al, 2000) . Previous studies have shown that activated microglia contributes to the dopaminergic neuron degeneration in substantia nigra of PD patients (Caggiu et al, 2019) (Karaaslan et al, 2021), reports in murine PD models have also shown upregulation in AA signalling , concordant with these findings increased expression of genes encoding pro-inflammatory cytokines and AA signalling and various other key regulators in these pathways has been found in our analyses. Figure7D, shows a proposed model to explains the mechanism of CDK5/p25 mediated cPLA2 activation leading to neuroinflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Upregulation in the oxytocin signalling pathway is also seen to increase the expression of cPLA2 and also increase the calcium ion flux inside the cell (Soloff et al, 2000) . Previous studies have shown that activated microglia contributes to the dopaminergic neuron degeneration in substantia nigra of PD patients (Caggiu et al, 2019) (Karaaslan et al, 2021), reports in murine PD models have also shown upregulation in AA signalling , concordant with these findings increased expression of genes encoding pro-inflammatory cytokines and AA signalling and various other key regulators in these pathways has been found in our analyses. Figure7D, shows a proposed model to explains the mechanism of CDK5/p25 mediated cPLA2 activation leading to neuroinflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Although no remarkable difference of Tregs fractions was observed in the blood of patients with PD (Cen et al, 2017), others found CD49d + Tregs increased in PD compared to that in HC (Karaaslan et al, 2021). Tregs dysregulation and its impaired function of suppressing the activation of effector T cells were linked to the pathology of PD and disease severity The biological process of the GO enrichment analysis of filtered genes in green and cyan modules, separately.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these cells were observed to preferentially differentiate towards a Th1-reactive state [ 58 ]. Recent PD research also showed differentially expressed genes in peripheral blood mononuclear cells (PBMCs), with patients presenting an elevated abundance of CD49d+ Treg cells, which are known to suppress inflammatory processes [ 59 ]. When investigating the interaction of microglia and peripheral immune cells in PD, a recent study in rats found an important role of infiltrating T cells.…”
Section: (Neuro) Inflammation In Pdmentioning
confidence: 99%